Evaluation of control and modulation methods for modular multilevel converters - Siemaszko, Daniel; Antonopoulos, Antonios; Ilves, Kalle; Vasiladiotis, Michail; Ängquist, Lennart; Nee, Hans-Peter (2010 International Power Electronics Conference, 2010)
The modular multilevel converter is a promising converter technology for various high-voltage high-power applications. Despite the apparent simplicity of the circuit, the inherent dynamics of the converter and the balancing of the sub-module capacitor voltages impose high requirements on the control system, which can be implemented in quite different ways. To illustrate this, and to provide a guidance for future research on the subject, this paper presents an evaluation of four different control and modulation methods. The investigation is based on experiments on a down-scaled 10 kVA converter having 10 submodules per phase leg. The main items to be investigated are dynamics within the sub-modules, arm voltages and circulating currents. It is found that the suggested open-loop control method provides the fastest arm-voltage response and that the balancing approach based on a sorting algorithm is substantially faster and less complicated to implement than the method using a dedicated voltage controller for each sub-module.